2022
DOI: 10.4084/mjhid.2022.052
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of ineffective erythropoiesis biomarkers and development of extramedullary hematopoiesis in patients with thalassemia

Abstract: Introduction: Extramedullary hematopoiesis (EMH) is one of the main complications in patients with thalassemia in compensation for the underlying ineffective erythropoiesis. This study aimed to evaluate the association between ineffective erythropoiesis biomarkers and EMH in patients with thalassemia. Methods: A cross-sectional study of thalassemia patients aged >18 years old at Srinagarind Hospital was performed. Phosphatidylserine-exposed red blood cells (PS-exposed RBCs) were studied by flow cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Another potential explanation is the impact of altered erythropoiesis on lipid metabolism. Alpha-thalassemia affects red blood cell production and can lead to ineffective erythropoiesis, where a higher number of immature red blood cells are produced ( 36 ). This altered erythropoiesis may disrupt normal lipid metabolism and result in lower levels of TG as observed in the coexistence of alpha-thalassemia in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential explanation is the impact of altered erythropoiesis on lipid metabolism. Alpha-thalassemia affects red blood cell production and can lead to ineffective erythropoiesis, where a higher number of immature red blood cells are produced ( 36 ). This altered erythropoiesis may disrupt normal lipid metabolism and result in lower levels of TG as observed in the coexistence of alpha-thalassemia in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies in the literature measuring CEC levels in β‐thalassemia patients [ 17 , 18 ]. In our study, we found that CEC levels in patients with βThal were significantly higher than the control group.…”
Section: Discussionmentioning
confidence: 99%